2014
DOI: 10.15740/has/tajh/9.2/386-389
|View full text |Cite
|
Sign up to set email alerts
|

Response of french bean (Phaseolus vulgaris L.) to organic manure, vermicompost and biofertilizers on growth parameters and yield

Abstract: : A field experiment was conducted at farmer's field during Rabi season of 2011-12 in Jorhat district to study the effect of different combinations of organic sources of nutrients viz., vermicompost, FYM, rock phosphate along with bio-fertilizer on different growth parameters, yield and profitability of French bean cultivar Arka Anoop. The experiment was laid out in Randomized Block Design with four treatments and five replications. In this investigation, the results revealed that application of vermicompost +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…El-Bassiony et al, (2010), Sarmaet al, (2014 and Zahida et al, (2016) The increase in yield attributes might have been due to increased availability of NPK, higher total dry matter production and more vegetative growth resulting in better development of yield attributes and higher seed yield with application of heavy inorganic fertilization. Prabhakar et al, (2011), Sarma et al, (2014 and Meena et al, (2018) and Sharma et al, (2017) found in their research that the yield and yield components were significantly increased by the application of chemicals and bio-regulators.…”
Section: Growth Charactersmentioning
confidence: 98%
“…El-Bassiony et al, (2010), Sarmaet al, (2014 and Zahida et al, (2016) The increase in yield attributes might have been due to increased availability of NPK, higher total dry matter production and more vegetative growth resulting in better development of yield attributes and higher seed yield with application of heavy inorganic fertilization. Prabhakar et al, (2011), Sarma et al, (2014 and Meena et al, (2018) and Sharma et al, (2017) found in their research that the yield and yield components were significantly increased by the application of chemicals and bio-regulators.…”
Section: Growth Charactersmentioning
confidence: 98%
“…those are directly involved with the improvement of yield and quality [13]. These finding of the positive effect of the organic supplement on crop production conformed with Thakur et al [14], Sharma et al [15], Selim et al [16], Simarmata et al [17], Nurhidayatia et al [18], Islam et al [19], Jesu [20], Ranjit et al [21], Sarma et al [22], Farahzety and Aishah [23], Prabhakar et al [24] and Singh et al [25].…”
Section: French Beanmentioning
confidence: 56%
“…Organic nutrient management is considered an important activity, as it helps to enhance the growth and productivity of the French bean crop and to improve the physical, chemical, and biological properties of soil (Singh et al, 2018). In French beans, instead of a single source of nutrients, applying different organic sources of nutrients in an integrated manner has been shown to increase crop productivity and improve soil health (Sharma et al, 2014;Singh et al, 2016). The constant supply of nutrients through organic sources into the active nutrients pool of soils developed a vigorous root system, resulting in the better growth and development of plants and better diversion of photosynthates from the source to sink; thus, the combined use of organic sources might be much more advantageous for healthy growth and timely flowering in crops (Aziz et al, 2019;Ghani et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…The integrated supply of the recommended nitrogen dose through FYM, MC, and VC (FYM 33% + MC 33% + VC 33% RDN) increased the plant height and duration of days to 50% flowering compared to single source. The integration of vermicompost, FYM, rock phosphate, and Rhizobium facilitates the adequate nutrient supply to French bean, resulting in better crop growth (Sharma et al, 2014). In contrast, the significantly poor French bean growth under the suboptimal nutritional treatment may have been because the root system might not have been active for efficient nutrient uptake during the period of active crop growth and development stages, resulting in reduced plant height and the crop reaching an early flowering stage (Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%